ANALISIS JENIS KELAMIN DAN KEBIASAAN JAJAN DENGAN KEJADIAN ISPA PADA ANAK DI TK DHARMA WANITA PERSATUAN UNIT SIDOKLUMPUK SIDOARJO - Firdaus, Firdaus; Anindia Putri, Riska (Jurnal Ilmiah Kesehatan, 2016)
Many snacks are less qualified of health so they threaten children's health. This condition reflects the children become accustomed to eating bad snacks in the school environment. The purpose of this study was to determine the sex and the habit of eating snacks with upper respiratory tract infection occurrence on children in Dharma Wanita Persatuan Unit Kindergarten, Sidoklumpuk, Sidoarjo. The design of the study used an analytic-cross sectional approach. The population was the entire students in Dharma Wanita Persatuan Unit Kindergarten, Sidoklumpuk, Sidoarjo as 28 students, the sample which was 26 respondents was taken by using a simple random sampling technique. The independent variable was sex, snacks habit and the dependent variable was the occurrence of upper respiratory tract infection. The instruments used checklist and questionnaire. The data were analyzed by using spearmen rank test with a significance level (? = 0,05).The result of the study was the majority of the respondents (57.7%) was female and the majority of the respondents (53.8%) had a habit of eating bad snacks and almost half of the respondents (46.2%) was rare occurrence of URTI. Spearman Rank test result obtained that ? = 0,020, there was no correlation of sex with the upper respiratory tract infection occurrence in Dharma Wanita Persatuan Unit Kindergarten, Sidoklumpuk, Sidoarjo. Furthermore, it was obtained that 0,010 meant that there was correlation between the habit of eating snacks and the occurrence of URTI in Dharma Wanita Persatuan Kindergarten, Sidoklumpuk, Sidoarjo. The conclusion of the study was females most often consume foods which have striking colors, attractive appearances, sweet and savory flavors that are around the school so they will occur URTI. It is advised that parents encourage their children not to buy snacks and make the children become accustomed to having breakfast first.